2013
DOI: 10.1111/bph.12021
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PU.1‐linked TLR4 expression by cilostazol with decrease of cytokine production in macrophages from patients with rheumatoid arthritis

Abstract: BACKGROUND AND PURPOSEThe present study assessed the effects of cilostazol on LPS-stimulated TLR4 signal pathways in synovial macrophages from patients with rheumatoid arthritis (RA). These effects were confirmed in collagen-induced arthritis (CIA) in mice. EXPERIMENTAL APPROACHExpression of TLR4, PU.1, NF-kB p65 and IkBa on synovial fluid macrophages from RA patients was determined by Western blotting, and cytokines were measured by ELISA. Anti-arthritic effects were evaluated in CIA mice. KEY RESULTSIntracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…Recently, we further reported that cilostazol significantly suppressed LPS-induced TLR4 expression by blocking PU.1 transcriptional activity in synovial macrophages obtained from RA patients. In addition, cilostazol suppressed IκBα degradation, the nuclear translocation of NF-κB p65, associated with reduced production of the cytokines TNF-α and IL-1β [17]. Furthermore, synovial inflammation and bone erosion were significantly inhibited by cilostazol treatment in a murine CIA model.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, we further reported that cilostazol significantly suppressed LPS-induced TLR4 expression by blocking PU.1 transcriptional activity in synovial macrophages obtained from RA patients. In addition, cilostazol suppressed IκBα degradation, the nuclear translocation of NF-κB p65, associated with reduced production of the cytokines TNF-α and IL-1β [17]. Furthermore, synovial inflammation and bone erosion were significantly inhibited by cilostazol treatment in a murine CIA model.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 88%
“…Yang and Karsenty [12] emphasized that PU.1 is absolutely required for macrophage differentiation. Furthermore, Park et al [17] found that cilostazol down-regulated LPS-stimulated PU.1-linked TLR4 expression and NF-κB signal pathways, and then suppressed inflammatory cytokine production in synovial macrophages from RA patients and markedly inhibited the severity of CIA in mice. In the present study, we observed that cilostazol inhibited RANKL-induced RANK expression by inhibiting PU.1, which is consistent with a previous report by Kwon et al [13].…”
Section: Discussionmentioning
confidence: 99%
“…Cilostazol has also been shown to inhibit IFN-α and TNF-α production from plasmacytoid dendritic cells in a dosedependent manner [14]. In addition, cilostazol has been reported to suppress TNF-α and IL-1β production in synovial macrophages from RA patients via inhibition of TLR4/MyD88/ NF-κB signaling pathways [15]. Moreover, cilostazol inhibits TLR2-induced IL-23 production in human synovial macrophages by suppressing the RhoA pathway via a cAMP-dependent pathway [16].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 responsiveness is reported to play a role in the pathogenesis of other autoimmune diseases besides SLE including coxsackievirus-induced autoimmune myocarditis [132] collagen-induced arthritis [133], primary biliary cirrhosis [134], experimental autoimmune uveitis (EAU) [135], antibody-mediated glomerulonephritis [136] and autoimmune destructive arthritis [137]. However, most data were in mice; data in humans are largely lacking.…”
Section: Tlr4 Responsiveness and Monocyte Activation In Other Autoimmmentioning
confidence: 99%